Drug Discovery in Pharmaceutical Chemistry: An In-Depth Exploration - Patel, Shivkant; Dash, Dillip Kumar; Gohil, Dipti; Sen, Ashim Kumar; Sen, Dhanya B. (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
Drug discovery in pharmaceutical chemistry is a complex, multi-stage process aimed at identifying new compounds that can become effective therapeutic agents. This process involves several key phases: target identification and validation, hit identification, hit-to-lead development, lead optimization, preclinical development, and clinical development, culminating in regulatory approval. Each stage integrates diverse scientific disciplines and advanced technologies to ensure the discovery of viable drug candidates. Challenges such as high failure rates, complex disease biology, safety and toxicity concerns, and significant time and cost investments are inherent to this process. However, emerging trends like artificial intelligence, machine learning, personalized medicine, and the development of biologics and biosimilars are revolutionizing drug discovery, enhancing efficiency, and paving the way for more targeted and effective treatments. This exploration provides a detailed overview of each stage, highlights the associated challenges, and discusses the innovative trends that are shaping the future of pharmaceutical research.